The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000348431
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the Candidate Dyslexia Susceptibility Gene Homolog Dyx1c1 in Rodents: Effects on Auditory Processing, Visual Attention, and Cortical and Thalamic Anatomy

Abstract: The current study investigated the behavioral and neuroanatomical effects of embryonic knockdown of the candidate dyslexia susceptibility gene (CDSG) homolog Dyx1c1 through RNA interference (RNAi) in rats. Specifically, we examined long-term effects on visual attention abilities in male rats, in addition to assessing rapid and complex auditory processing abilities in male and, for the first time, female rats. Our results replicated prior evidence of complex acoustic processing deficits in Dyx1c1 male rats and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 85 publications
5
30
0
Order By: Relevance
“…A similar scenario was found for Dcdc2 when the knockout mouse for this gene was first characterised (Wang et al 2011), and for Dyx1c1 when a forebrain-conditional knockout mouse was analysed (Rendall et al 2015). Even though in utero electroporation in rat embryos of shRNAs against Dcdc2 (Meng et al 2005; Burbridge et al 2008; Adler et al 2013) or Dyx1c1 (Wang et al 2006; Threlkeld et al 2007; Szalkowski et al 2011, 2013) resulted in anatomical malformations, no migration deficits were found in Dcdc2 knockout or Emx1-Cre/Dyx1c1 flox/flox conditional knockout animals, nor in Dcdc2 floxed mice following acute elimination of the protein by Cre electroporation. In this particular case, the authors reported increased developmental defects in radial migration and dendritic growth of layer III neurons in Dcdc2 knockout animals upon RNA interference against Doublecortin ( Dcx ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar scenario was found for Dcdc2 when the knockout mouse for this gene was first characterised (Wang et al 2011), and for Dyx1c1 when a forebrain-conditional knockout mouse was analysed (Rendall et al 2015). Even though in utero electroporation in rat embryos of shRNAs against Dcdc2 (Meng et al 2005; Burbridge et al 2008; Adler et al 2013) or Dyx1c1 (Wang et al 2006; Threlkeld et al 2007; Szalkowski et al 2011, 2013) resulted in anatomical malformations, no migration deficits were found in Dcdc2 knockout or Emx1-Cre/Dyx1c1 flox/flox conditional knockout animals, nor in Dcdc2 floxed mice following acute elimination of the protein by Cre electroporation. In this particular case, the authors reported increased developmental defects in radial migration and dendritic growth of layer III neurons in Dcdc2 knockout animals upon RNA interference against Doublecortin ( Dcx ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of any of these genes yielded neuronal migration deficits. Effects on cognitive areas with potential relevance to dyslexia, such as working memory, auditory processing and visual attention, have been reported (162,163). However, it was recently shown that shRNA electroporation can produce neuronal migration deficits through off-target mechanisms distinct from gene-specific knockdown (12).…”
Section: Can Birdsong Inform the Neurogenetics Of Language?mentioning
confidence: 99%
“…Animal studies showed that memory-related behavioral phenotypes are associated with these genes (Tang et al 1999;Wang et al 2009;Szalkowski et al 2011Szalkowski et al , 2012Szalkowski et al , 2013. In particular, in utero RNAi of Dyx1c1 is related to deficits in spatial working memory performance (Szalkowski et al 2011(Szalkowski et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in utero RNAi of Dyx1c1 is related to deficits in spatial working memory performance (Szalkowski et al 2011(Szalkowski et al , 2013. Recently, Szalkowski and colleagues (2012) showed that embryonic RNAi of KIAA0319 expression resulted in spatial learning deficits.…”
Section: Discussionmentioning
confidence: 99%